Prevalence of primary immunodeficiency syndromes in tuberculous meningitis: A case-control study - Abhishek Shridhar; Ravindra Kumar Garg; Imran Rizvi; Mili Jain; Wahid Ali; Hardeep Singh Malhotra; Neeraj Kumar; Praveen Kumar Sharma; Rajesh Verma; Ravi Uniyal; Shweta Pandey (Elsevier, 2022)
Background: Only a proportion of patients with tuberculosis develop tuberculous meningitis. We hypothesize that inherent abnormalities in the host's innate or adaptive immune system may affect the outcome in tuberculous meningitis. In this study, we evaluated the proportion of underlying primary immunodeficiency in patients with tuberculous meningitis and its impact on the outcome. Methods: Newly-diagnosed cases with tuberculous meningitis and healthy controls were included. Patients with HIV disease were excluded. Blood specimen were subjected to immunological assessment to detect primary immunodeficiency syndrome/s. We estimated serum levels of IgG, IgA, IgM, IgE and IgD along with complement C3, C4, and C5 assay. Absolute lymphocyte count was obtained from an automated three-part cell counter. Flow cytometry was used to enumerate the following lymphocyte subsets: T Cell (CD3, CD4, CD8), B cell (CD19/CD20), and Natural killer cells (CD16 and CD56). Cases were followed for 6 months. Modified Barthel Index was used as a measure of disability. Results: We included 55 cases with tuberculous meningitis and 30 healthy controls. We notedthat among immune parameters, absolute lymphocyte count and CD4 T-cell count in the tuberculous meningitis group was lower; higher serum IgG levels were noted in the poor outcome group. On multivariate regression analysis, none of the immunological, clinical or radiological features were found to predict a poor outcome. Conclusion: Host's immune factors contribute to the pathogenesis of tuberculous meningitis. Absolute lymphocyte count and CD4+ T-cell count were lower in tuberculous meningitis cases. Higher serum IgG levels may be associated with a poor outcome. A study with a larger sample size is needed to confirm our findings.